Interior point method based contact analysis algorithm for structural analysis of electronic device models - Kazuhisa INAGAKI (The Japan Society of Mechanical Engineers, 2015)
In this paper, we present an algorithm for frictionless contact problems of linear elastic bodies with multi-point constraints. Our algorithm is based on an interior point method and is developed for large scale stress analysis of electronic device models. Electronic devices consist of dozens of thin parts such as liquid crystal displays, printed circuit boards and covers and these parts are placed layer by layer. Therefore, the finite element models contains so many discretized contact constraints and multi-point constraints that make convergence of contact states difficult to achieve. In our algorithm, multi-point constraints are removed by a quadratic penalty method at first, then a primal-dual interior point method is applied. We implemented our algorithm into FrontISTR, which is open-source and large scale finite element structural analysis software, and investigated its performance from simple contact models to actual electronic device models. The numerical experiments show that our algorithm is more efficient than an active set method with an penalty method for large models, although the convergency strongly depends on the parameter settings of a primal-dual interior point method.